Heterocyclic aroma-retaining slow-release Zn-doped ZIF-67 derivative adsorption material, preparation method thereof and application of heterocyclic aroma-retaining slow-release Zn-doped ZIF-67 derivative adsorption material in heating cigarettes
By preparing heterocyclic fragrance-protecting sustained release Zn-doped ZIF-67 derived adsorption materials, the problem of uneven release of fragrances in heating and non-combustible cigarettes is solved, the uniform release of aroma is achieved and the longevity of fragrance is extended, and the product quality is improved .
Patent Information
- Application Number
- CN202411693450.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-18
AI Technical Summary
The low boiling point and volatile characteristics of heterocyclic fragrances in cigarettes that do not burn, lead to uneven fragrance release and insufficient satisfaction. The problem of controlled release of fragrances and fragrances needs to be solved.
The heterocyclic fragrance-protective sustained release Zn-doped ZIF-67-derived adsorption material is used to prepare the material through coordination reaction and calcination, and the fragrance is loaded and adsorbed as a medium to achieve the protection and controlled release of fragrance is achieved.
Through the use of this material, the uniform release of aroma in the heating cigarette is ensured, the mouth-by-mouth decay speed of the fragrance is delayed, and the sensory experience of consumers is improved.
Smart Images

Figure CN119455914A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of tobacco materials, and in particular to a heterocyclic flavor-preserving sustained-release Zn-doped ZIF-67 derived adsorption material, a preparation method thereof, and application thereof in heated cigarettes. Background Art
[0002] Heat-not-burn cigarettes are new tobacco products that have been highly valued in recent years. Compared with traditional cigarettes, they are less harmful and safer, and have gradually become a hot spot for the growth of international tobacco consumption. When smoking, the tobacco leaves are heated with heating appliances, and the controlled-release materials of the tobacco absorb the flavors, so that the flavor is released evenly, thereby improving the consistency of each puff of the heated cigarette during the smoking process, which can better meet the physiological and psychological needs of consumers.
[0003] However, due to their low boiling point and volatility, heterocyclic flavors have greatly reduced their application effect in heated cigarettes. In addition, the release mechanism of heterocyclic flavor substances in heated cigarettes is different from that of traditional cigarettes. In traditional cigarettes, flavor substances are mainly generated and released above 600°C, while the heating temperature of heat-not-burn cigarettes is generally around 300°C, which is lower than the combustion temperature of traditional cigarettes. The lower temperature affects the transfer of flavor substances, and the amount of generation and release will be greatly reduced, resulting in insufficient flavor satisfaction in heated cigarettes. Therefore, it is urgent to solve the problem of controlled release of flavors and fragrances in heat-not-burn tobacco products. Summary of the invention
[0004] The purpose of the present invention is to provide a heterocyclic flavor-preserving sustained-release Zn-doped ZIF-67 derived adsorbent material, a preparation method thereof, and an application thereof in heated cigarettes. The prepared adsorbent material is used as a medium to load flavors and fragrances to achieve protection and controlled release of flavors and fragrances, so as to ensure uniformity of aroma release before and after smoking, give the product a characteristic aroma style, and improve the quality of heated non-burning cigarettes.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] A method for preparing a heterocyclic aroma-preserving sustained-release Zn-doped ZIF-67 derived adsorption material comprises the following steps:
[0007] mixing the cobalt salt, the zinc salt and water to obtain a mixed salt solution;
[0008] Mixing 2-methylimidazole, hexadecyltrimethylammonium bromide and water to obtain a mixed solution;
[0009] The mixed salt solution is mixed with the mixed liquid to carry out coordination reaction, and the obtained product is roasted to obtain a heterocyclic aroma-preserving sustained-release Zn-doped ZIF-67 derived adsorption material.
[0010] Preferably, the molar ratio of the cobalt salt to the zinc salt is (3-32):1.
[0011] Preferably, the molar ratio of the 2-methylimidazole to the cobalt salt is (56-73):1; the mass ratio of the 2-methylimidazole to hexadecyltrimethylammonium bromide is 5-10:0.01.
[0012] Preferably, the temperature of the coordination reaction is 20-25° C., and the time is 10-60 min; the temperature of the calcination is 300-400° C., and the time is 1-3 h.
[0013] The present invention provides a heterocyclic aroma-preserving sustained-release Zn-doped ZIF-67 derived adsorption material prepared by the preparation method described in the above technical scheme.
[0014] The present invention provides the use of the heterocyclic flavor-preserving sustained-release Zn-doped ZIF-67 derived adsorption material described in the above technical solution in heated cigarettes.
[0015] Preferably, the application method comprises the following steps:
[0016] The heterocyclic fragrance-preserving sustained-release Zn-doped ZIF-67-derived adsorption material and heterocyclic fragrances are placed in the same closed environment for adsorption.
[0017] Preferably, the heterocyclic fragrance includes one of 3-acetylpyridine, 2-acetylpyridine, 2-acetylpyrrole and 2,3,5-trimethylpyrazine.
[0018] Preferably, the usage ratio of the heterocyclic fragrance-preserving sustained-release Zn-doped ZIF-67-derived adsorption material to the heterocyclic fragrance is 30-60 mg: 100-300 μL.
[0019] Preferably, the adsorption temperature is 50-100° C., and the adsorption time is 5-10 h.
[0020] The present invention provides a method for preparing a heterocyclic aroma-preserving sustained-release Zn-doped ZIF-67 derived adsorbent material. Zn is doped in the preparation process of ZIF-67, and a Co-doped Zn-doped ZIF-67 adsorbent material is obtained by calcining. a Zn b O x The flavoring adsorption material is based on the skeleton. The product obtained by using the material to adsorb the flavor has the characteristic aroma of baking. The adsorption material is added to the heated cigarette to adsorb the flavor substances, so that the flavor releases the aroma slowly during the heating process, achieving a slow-release effect, which can effectively reduce the flavor decay speed from puff to puff and improve the sensory experience of consumers.
[0021] In the heterocyclic flavor-preserving sustained-release material prepared by the present invention, the morphology structure and specific surface area of the material are regulated by Zn doping, thereby improving the adsorption performance and sustained-release performance. Compared with undoped Co3O4, the Zn-doped material exhibits higher adsorption capacity. The adsorption of heterocyclic flavors by Zn-doped Co3O4 materials includes physical adsorption (such as surface adsorption) and chemical adsorption (such as the formation of chemical bonds). This dual adsorption mechanism may help the material achieve a higher adsorption amount and better selectivity. Therefore, the Zn-doped ZIF-67-derived adsorption material prepared by the present invention has excellent performance in adsorption capacity and sustained-release effect, and will have broad application prospects in the fields of cigarette flavoring, daily chemical products, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the SEM image of the material prepared in Comparative Example 1;
[0023] Figure 2 The SEM images of the Zn-doped ZIF-67 derived adsorption materials prepared in Examples 1 to 6;
[0024] Figure 3 Co6Zn1O x FTIR images before and after adsorption of 3-acetylpyridine;
[0025] Figure 4 (a) Standard curve of 3-acetylpyridine, (b) Co6Zn1O x GC-MS graph after adsorption of 3-acetylpyridine fragrance;
[0026] Figure 5 (a) The amount of fragrance adsorbed by the four adsorbent materials; (b) The fragrance retention rate of the four adsorbent materials after 20 days of release. DETAILED DESCRIPTION
[0027] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.
[0028] The present invention provides a method for preparing a heterocyclic aroma-preserving sustained-release Zn-doped ZIF-67 derived adsorption material, comprising the following steps:
[0029] mixing the cobalt salt, the zinc salt and water to obtain a mixed salt solution;
[0030] Mixing 2-methylimidazole, hexadecyltrimethylammonium bromide and water to obtain a mixed solution;
[0031] The mixed salt solution is mixed with the mixed liquid to carry out coordination reaction, and the obtained product is roasted to obtain a heterocyclic aroma-preserving sustained-release Zn-doped ZIF-67 derived adsorption material.
[0032] In the present invention, the cobalt salt is preferably cobalt nitrate, and the zinc salt is preferably zinc nitrate or zinc acetate.
[0033] In the present invention, the molar ratio of the cobalt salt to the zinc salt is preferably (3-32):1, more preferably (6-24):1, and further preferably (12-18):1.
[0034] In the present invention, the molar ratio of the 2-methylimidazole to the cobalt salt is preferably (56-73):1, more preferably (57-64):1, and further preferably (58-59):1; the mass ratio of the 2-methylimidazole to hexadecyltrimethylammonium bromide is preferably 5-10:0.01, and more preferably 9.08:0.01.
[0035] The present invention has no particular limitation on the amount of water used to prepare the mixed salt solution and the mixed solution, and the amount can be adjusted according to actual needs to ensure that the reaction proceeds smoothly.
[0036] The present invention preferably mixes the mixed salt solution with the mixed liquid, and then preferably performs coordination reaction under stirring conditions, washes the obtained solid product twice by ethanol centrifugation at 9000 rpm for 20 minutes, places it in a 60°C oven for 12 hours, and roasts the obtained product in a muffle furnace.
[0037] In the present invention, the temperature of the coordination reaction is preferably 20-25°C, the time is preferably 10-60 min, and more preferably 20-30 min; the calcination temperature is preferably 300-400°C, more preferably 350-400°C, the time is preferably 1-3 h, and more preferably 2 h; the present invention preferably heats from room temperature to the calcination temperature at a rate of 1°C / min.
[0038] The present invention provides a heterocyclic aroma-preserving sustained-release Zn-doped ZIF-67 derived adsorption material prepared by the preparation method described in the above technical scheme.
[0039] The present invention provides the use of the heterocyclic flavor-preserving sustained-release Zn-doped ZIF-67 derived adsorption material described in the above technical solution in heated cigarettes.
[0040] In the present invention, the method of application preferably comprises the following steps:
[0041] The heterocyclic fragrance-preserving sustained-release Zn-doped ZIF-67-derived adsorption material and heterocyclic fragrances are placed in the same closed environment for adsorption.
[0042] In the present invention, the heterocyclic fragrance includes one of 3-acetylpyridine, 2-acetylpyridine, 2-acetylpyrrole and 2,3,5-trimethylpyrazine.
[0043] In the present invention, the usage ratio of the heterocyclic fragrance-preserving sustained-release Zn-doped ZIF-67-derived adsorbent material to the heterocyclic fragrance is 30-60 mg:100-300 μL, more preferably 50 mg:200 μL.
[0044] In the present invention, the adsorption temperature is preferably 50-100° C., more preferably 80° C., and the adsorption time is preferably 5-10 h, more preferably 8 h.
[0045] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0046] Example 1
[0047] Take 1.9394mmol Co(NO3)2·6H2O and 0.0606mmol(CH3COO)2Zn and dissolve them in 20mL deionized water, dissolve 9.08g 2-methylimidazole and 10mg hexadecyltrimethylammonium bromide (CTAB) in 80mL deionized water, mix the two solutions and vigorously stir them at 25℃ for 20min to obtain a purple solid, then wash it twice by ethanol centrifugation at 9000rpm for 20min, and place it in a 60℃ oven for 12h. The obtained product is calcined in a muffle furnace, starting from room temperature and rising to 400℃ at a rate of 1℃ / min, and kept warm for 2h to obtain a Zn-doped ZIF-67 derived adsorption material (the molar ratio of Co to Zn is 32:1).
[0048] Example 2
[0049] 1.9200mmol Co(NO3)2·6H2O and 0.0800mmol(CH3COO)2Zn were dissolved in 20mL deionized water, 9.08g 2-methylimidazole and 10mg hexadecyltrimethylammonium bromide (CTAB) were dissolved in 80mL deionized water, the two solutions were mixed and vigorously stirred at 25°C for 20min to obtain a purple solid, which was then washed twice by ethanol centrifugation at 9000rpm for 20min and placed in a 60°C oven for 12h. The resulting product was calcined in a muffle furnace, starting from room temperature and rising to 400°C at a rate of 1°C / min, and kept warm for 2h to obtain a Zn-doped ZIF-67 derived adsorption material (the molar ratio of Co to Zn was 24:1).
[0050] Example 3
[0051] 1.8947mmol Co(NO3)2·6H2O and 0.1053mmol (CH3COO)2Zn were dissolved in 20mL deionized water, 9.08g 2-methylimidazole and 10mg hexadecyltrimethylammonium bromide (CTAB) were dissolved in 80mL deionized water, the two solutions were mixed and vigorously stirred at 25°C for 20min to obtain a purple solid, which was then washed twice by ethanol centrifugation at 9000rpm for 20min and placed in a 60°C oven for 12h. The resulting product was calcined in a muffle furnace, starting from room temperature and rising to 400°C at a rate of 1°C / min, and kept warm for 2h to obtain a Zn-doped ZIF-67 derived adsorption material (the molar ratio of Co to Zn was 18:1).
[0052] Example 4
[0053] 1.8462mmol Co(NO3)2·6H2O and 0.1538mmol (CH3COO)2Zn were dissolved in 20mL deionized water, 9.08g 2-methylimidazole and 10mg hexadecyltrimethylammonium bromide (CTAB) were dissolved in 80ml deionized water, the two solutions were mixed and vigorously stirred at 25°C for 20min to obtain a purple solid, which was then washed twice by ethanol centrifugation at 9000rpm for 20min and placed in a 60°C oven for 12h. The obtained product was calcined in a muffle furnace, starting from room temperature and rising to 400°C at a rate of 1°C / min, and kept warm for 2h to obtain a Zn-doped ZIF-67 derived adsorbent material (the molar ratio of Co to Zn was 12:1, denoted as Co 12 Zn1O x ).
[0054] Example 5
[0055] 1.7143mmol Co(NO3)2·6H2O and 0.2857mmol (CH3COO)2Zn were dissolved in 20mL deionized water, 9.08g 2-methylimidazole and 10mg hexadecyltrimethylammonium bromide (CTAB) were dissolved in 80ml deionized water, the two solutions were mixed and vigorously stirred at 25℃ for 20min to obtain a purple solid, which was then washed twice by ethanol centrifugation at 9000rpm for 20min and placed in a 60℃ oven for 12h. The obtained product was calcined in a muffle furnace, starting from room temperature and rising to 400℃ at a rate of 1℃ / min, and kept warm for 2h to obtain a Zn-doped ZIF-67 derived adsorbent material (the molar ratio of Co to Zn was 6:1, denoted as Co6Zn1O x ).
[0056] Example 6
[0057] 1.5000mmol Co(NO3)2·6H2O and 0.5000mmol(CH3COO)2Zn were dissolved in 20mL deionized water, 9.08g 2-methylimidazole and 10mg hexadecyltrimethylammonium bromide (CTAB) were dissolved in 80mL deionized water, the two solutions were mixed and vigorously stirred at 25°C for 20min to obtain a purple solid, which was then washed twice by ethanol centrifugation at 9000rpm for 20min and placed in a 60°C oven for 12h. The obtained product was calcined in a muffle furnace, starting from room temperature and rising to 400°C at a rate of 1°C / min, and kept warm for 2h to obtain a Zn-doped ZIF-67 derived adsorbent material (the molar ratio of Co to Zn was 3:1, denoted as Co3Zn1O x ).
[0058] Comparative Example 1
[0059] Take 2mmol Co(NO3)2·6H2O and dissolve it in 20mL deionized water, dissolve 9.08g 2-methylimidazole and 10mg hexadecyltrimethylammonium bromide (CTAB) in 80mL deionized water, mix the two solutions and vigorously stir them at 25℃ for 20min to obtain a purple solid, then wash it twice by ethanol centrifugation at 9000rpm for 20min, place it in a 60℃ oven for 12h, and calcine the obtained product in a muffle furnace, starting from room temperature and rising to 400℃ at a rate of 1℃ / min, and keep it warm for 2h to obtain Co3O4.
[0060] Characterization and performance testing
[0061] 1) Figure 1 This is the SEM image of the Co3O4 material prepared in Comparative Example 1. Figure 1 It can be seen that Co3O4 has a cubic structure with a rough surface and abundant pores.
[0062] 2) Figure 2 The SEM images of the materials prepared in Examples 1 to 6 are shown in FIG. Figure 2 It can be seen that with the increase of Zn doping content, the formed adsorbed material gradually becomes square and three-dimensional with clear and full outlines, and the best morphology effect is achieved when Co:Zn is 6:1. When the Zn doping content is further increased and Co:Zn reaches 3:1, the cubic structure disappears, which may be the limiting ratio of Zn doping.
[0063] 3) The materials prepared in Comparative Example 1 and Examples 4 to 6 were subjected to BET test. The results are shown in Table 1.
[0064] Table 1 Structural parameters of different adsorption materials
[0065]
[0066] As shown in Table 1, the specific surface areas of the three Zn-doped materials have increased. The increase in specific surface area means that there are more areas that can contact with 3-acetylpyridine fragrance, thereby increasing the possibility of adsorption. At the same time, more adsorption sites (provided by the rough surface and possible pore structure) also mean that more fragrance molecules can be adsorbed. The reduction in grain size helps to increase the specific surface area and the exposure of active sites, which is beneficial to the adsorption of fragrance. Co6Zn1O x The crystal size of Co is the smallest and the specific surface area is the largest, so it may be more conducive to the adsorption of fragrances. 12 Zn1O x The specific surface area is second, Co3Zn1O x It is smaller than the above two materials, but has a larger specific surface area than Co3O4.
[0067] 2) Adsorption performance test:
[0068] Weigh 50 mg of each material sample prepared in different cases and put them into different watch glasses. Then weigh 3-acetylpyridine fragrance (200 μL) into the watch glass. Put the watch glass containing the material sample and the container containing 3-acetylpyridine into a sealed container. Make sure that the sealed container is completely sealed to prevent the fragrance from volatilizing to the outside during the adsorption process. Place the sealed container in an oven at 80°C for an adsorption experiment. The adsorption time is 8 hours to ensure that the fragrance molecules have enough time to diffuse into the pores of the material. Co a Zn b O x / FG materials, and the dried samples were collected for sustained-release experiments and characterization.
[0069] Figure 3 Co6Zn1O x FTIR images before and after adsorption of 3-acetylpyridine, characterizing Co6Zn1O x The adsorption capacity of the material for 3-acetylpyridine fragrance and its interaction with fragrance molecules. x The infrared spectra of the material before and after the adsorption of 3-acetylpyridine show the changes in peak intensity at certain specific wave numbers. Figure 3 As shown, the material appears at 1500-1350cm -1 The characteristic peak at can be attributed to the stretching vibration of the imidazole ring. x The main absorption peak of the material is related to 2-methylimidazole, and it also proves that Co6Zn1O x Successful synthesis of materials. Figure 3 The stretching vibration of C=O characteristic peak of 3-acetylpyridine appears at 1684 cm -1At Co6Zn1O x The C=O characteristic peak of 3-acetylpyridine after material adsorption appears at 1691 cm -1 This phenomenon may be related to the MC chemical bond formed by the C-terminus of 3-acetylpyridine and the metal atom. The results show that there is a strong interaction between Zn-doped Co3O4 and 3-acetylpyridine, which is mainly adsorbed through hydrogen bonds and van der Waals forces. This adsorption method helps to achieve stable and sustained release of spices. x In addition to physical adsorption, the material also has chemical adsorption for 3-acetylpyridine.
[0070] Gas chromatography is used to detect the material. The specific operation is as follows:
[0071] First, 3-acetylpyridine was diluted to a fixed volume with anhydrous ethanol to draw a standard curve of 3-acetylpyridine ( Figure 4 (a)). Weigh 5 mg of the material after the flavor adsorption, add the weighed sample into 2 mL of ethanol solution, and use an ultrasonic cleaner to ultrasonically treat for 30 min at 40°C to promote the release of 3-acetylpyridine from the material into the ethanol solution. Place the mixture after ultrasonic treatment in a centrifuge and centrifuge at 8000 rpm for 5 min. Take the supernatant after centrifugation and test the supernatant after centrifugation using a gas chromatograph-mass spectrometer. Substitute the results into the standard curve and the adsorption amount formula (1) for calculation.
[0072]
[0073] The gas chromatography conditions are as follows: the temperature was programmed to rise, with an initial temperature of 40°C, a holding time of 3 min, a temperature rise of 10°C / min to 180°C, and a holding time of 30 min. The carrier gas (He) flow rate was 1.0 mL / min, and the purity was 99.99%. The injection mode was splitless. The ion source temperature was 230°C, and the transfer line temperature was 260°C. The scanning modes were full scan and selective scan. The solution delay was 5 min.
[0074] Figure 4 (a) Standard curve of 3-acetylpyridine, (b) Co6Zn1O x GC-MS chart after adsorption of 3-acetylpyridine fragrance; Figure 4 It can be seen that adsorption does not change the properties of the fragrance.
[0075] The adsorption of 3-acetylpyridine by the four materials prepared in Comparative Example 1 and Examples 4 to 6 was tested. The results are as follows: Figure 5As shown in (a) (the adsorption capacity of fragrances by four adsorbent materials), the materials synthesized with different Co:Zn ratios have different adsorption capacities for 3-acetylpyridine. Compared with the adsorption capacity of 3-acetylpyridine by Co3O4 (29.35 μL / g), the adsorption capacities of the other three Zn-doped materials are all improved, among which Co6Zn1O with a Co:Zn ratio of 6:1 has a higher adsorption capacity than Co3O4 (29.35 μL / g). x It showed the highest adsorption capacity of 3-acetylpyridine, with an adsorption capacity of 44.04 μL / g, exceeding that of Co3Zn1O with a Co:Zn ratio of 3:1 and 12:1. x (32.60 μL / g) and Co 12 Zn1O x (40.65μL / g). The adsorption capacity of the four materials is ranked from high to low as follows: Co6Zn1O x >Co 12 Zn1O x >Co3Zn1O x >Co3O4. The adsorption of 3-acetylpyridine by the three Zn-doped materials is 1.5 times, 1.38 times, and 1.11 times that of Co3O4, respectively. Figure 5 As can be seen from (a), within a certain range (from Co 12 Zn1O x to Co6Zn1O x ), as the ratio of Co to Zn changes from 12:1 to 6:1, the adsorption capacity of the material for fragrance increases from 40.65 μL / g to 44.04 μL / g, indicating that within this range, the increase in the amount of Zn doping is beneficial to improving the adsorption capacity of the material. When it exceeds a certain limit (such as Co3Zn1O x ), as the Zn doping amount increases, the fragrance adsorption amount will decrease (30.60μL / g), indicating that the more Zn doping amount, the better. x It is the material with the best adsorption performance.
[0076] Controlled release experiment
[0077] The adsorbed material was placed in a constant temperature environment at 25°C to ensure that the environment was stable and not disturbed by external factors (such as light, humidity changes, etc.). After 20 days, the sample was taken out and the remaining 3-acetylpyridine fragrance content in the material was determined. The data was substituted into the following formula (2) to calculate the retention rate.
[0078]
[0079] Gas chromatography-mass spectrometry was used to detect Co3O4 / FG, Co 12 Zn1O x / FG、Co6Zn1O x / FG、Co3Zn1O x / FG sustained release of fragrance for 20 days at room temperature 25℃, Figure 5 (b) shows the fragrance retention rate of the four adsorbent materials after 20 days of release. Figure 5 As shown in (b), the sustained release performance of materials synthesized with different Co and Zn ratios after adsorbing 3-acetylpyridine is different; after 20 days of sustained release, Co3O4, Co 12 Zn1O x 、Co6Zn1O x 、Co3Zn1O x The retention rates of the fragrance molecules are approximately 22.49%, 74.73%, 95.67%, and 32.49%, and the sustained release performance is ranked from high to low as Co6Zn1O x >Co 12 Zn1O x >Co3Zn1O x >Co3O4, the fragrance retention rates of the three materials doped with Zn are 4.25 times that of Co3O4 (Co6Zn1O x ), 3.22 times (Co 12 Zn1O x ), 1.44 times (Co3Zn1O x ). Therefore, it can be concluded that Zn doping greatly improves the sustained release performance of Co3O4 derived from ZIF-67. Figure 5 As can be seen from (b), within a certain range (from Co 12 Zn1O x to Co6Zn1O x ), as the Zn doping amount increases, the retention rate of 3-acetylpyridine in the material also increases. When it exceeds a certain limit (such as Co3Zn1O x ), as the doping amount of Zn increases, the retention rate of the fragrance 3-acetylpyridine will decrease. x It is the best material for sustained release performance.
[0080] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a heterocyclic aroma-preserving sustained-release Zn-doped ZIF-67 derived adsorption material, comprising the following steps: mixing the cobalt salt, the zinc salt and water to obtain a mixed salt solution; Mixing 2-methylimidazole, hexadecyltrimethylammonium bromide and water to obtain a mixed solution; The mixed salt solution is mixed with the mixed liquid to carry out coordination reaction, and the obtained product is roasted to obtain a heterocyclic aroma-preserving sustained-release Zn-doped ZIF-67 derived adsorption material.
2. The preparation method according to claim 1, characterized in that: The molar ratio of the cobalt salt to the zinc salt is (3-32):
1.
3. The preparation method according to claim 1, characterized in that: The molar ratio of the 2-methylimidazole to the cobalt salt is (56-73) 1; the mass ratio of the 2-methylimidazole to hexadecyltrimethylammonium bromide is 5-10:0.
01.
4. The preparation method according to claim 1, characterized in that: The temperature of the coordination reaction is 20-25° C., and the time is 10-60 minutes; the temperature of the calcination is 300-400° C., and the time is 1-3 hours.
5. The heterocyclic aroma-preserving sustained-release Zn-doped ZIF-67 derived adsorption material prepared by the preparation method according to any one of claims 1 to 4.
6. Use of the heterocyclic flavor-preserving sustained-release Zn-doped ZIF-67 derived adsorption material according to claim 5 in heated cigarettes.
7. The use according to claim 6, characterized in that: The method of application comprises the following steps: The heterocyclic fragrance-preserving sustained-release Zn-doped ZIF-67-derived adsorption material and heterocyclic fragrances are placed in the same closed environment for adsorption.
8. The use according to claim 7, characterized in that: The heterocyclic fragrance includes one of 3-acetylpyridine, 2-acetylpyridine, 2-acetylpyrrole and 2,3,5-trimethylpyrazine.
9. The use according to claim 7, characterized in that: The usage ratio of the heterocyclic fragrance-preserving sustained-release Zn-doped ZIF-67-derived adsorption material to the heterocyclic fragrance is 30-60 mg: 100-300 μL.
10. The use according to claim 7, characterized in that: The adsorption temperature is 50-100° C., and the adsorption time is 5-10 hours.